Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $G$ be an arbitrary group with identity element $e$ and let $K$ and $N$ be normal subgroups of G with $K∩N={e}$.

I know that $nk=nk$ And the representation of an element in $K×N$ in form $kn$ is unique for all $k∈K$ and $n∈N$.

How can I show the function

$φ:(K×N)→(K⊕N)$ be defined by $φ(kn)=(k,n)$.

is well defined?

I know that I need to show for all $kn,xy∈K×N$ such that $kn=xy$, $φ(kn)=φ(xy)$ But I don't know how to show that

share|cite|improve this question
I think your third line should begin with "I know that $\,nk=kn\,$ ..." , and not what you wrote... – DonAntonio Apr 20 '13 at 14:01
up vote 2 down vote accepted

If $kn=xy$, then $x^{-1}k = yn^{-1}$. Since the left hand side is in $K$ and the right hand side is in $N$, both are in $K\cap N=\{e\}$. Hence $x^{-1}k=e=yn^{-1}$ and we conclude $x=k$ and $y=n$.

Thus, $\phi(xy) = \phi(kn)$ by the substitution property of equality.

share|cite|improve this answer

\begin{alignat*}{4} &\text{If}\quad &&k_1n_1=k_2n_2 \\ &\Rightarrow {} &&k_2^{-1}k_1=n_2n_1^{-1}=e \quad\quad&&(K\cap N =\{e \}) \\ &\Rightarrow {} &&k_1=k_2 \land n_1=n_2 &&\text{}\\ &\Rightarrow {} &&(k_1,n_1)=(k_2,n_2) &&\text{}\\ &\Rightarrow {} &&\varphi(k_1n_1)=\varphi (k_2n_2) &&\text{}\\ \end{alignat*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.